Integrating multiple data sources to assess the distribution and abundance of bottlenose dolphins Tursiops truncatus in Scottish waters. (6th February 2012) - Cheney, Barbara; Thompson, Paul M.; Ingram, Simon N.; Hammond, Philip S.; Stevick, Peter T.; Durban, John W.; Culloch, Ross M.; Elwen, Simon H.; Mandleberg, Laura; Janik, Vincent M.; Quick, Nicola J.; ISLAS‐Villanueva, Valentina; et al.
Abstract The distribution, movements and abundance of highly mobile marine species such as bottlenose dolphins Tursiops truncatus are best studied at large spatial scales, but previous research effort has generally been focused on relatively small areas, occupied by populations with high site fidelity. We aimed to characterize the distribution, movements and abundance of bottlenose dolphins around the coasts of Scotland, exploring how data from multiple sources could be integrated to build a broader‐scale picture of their ecology. We reviewed existing historical data, integrated data from ongoing studies and developed new collaborative studies to describe distribution patterns. We adopted a Bayesian multi‐site mark‐recapture model to estimate abundance of bottlenose dolphins throughout Scottish coastal waters and quantified movements of individuals between study areas. The majority of sightings of bottlenose dolphins around the Scottish coastline are concentrated on the east and west coasts, but records are rare before the 1990s. Dedicated photo‐identification studies in 2006 and 2007 were used to estimate the size of two resident populations: one on the east coast from the Moray Firth to Fife, population estimate 195 [95% highest posterior density intervals (HPDI): 162–253] and the second in the Hebrides, population estimate 45 (95% HPDI: 33–66). Interaction parameters demonstrated that the dolphins off the east coast of Scotland are highly mobile, whereas those off the west coast form two discrete communities. We provide the first comprehensive assessment of the abundance of bottlenose dolphins in the inshore waters of Scotland. The combination of dedicated photo‐identification studies and opportunistic sightings suggest that a relatively small number of bottlenose dolphins (200–300 individuals) occur regularly in Scottish coastal waters. On both east and west coasts, re‐sightings of identifiable individuals indicate that the animals have been using these coastal areas since studies began.